2000
DOI: 10.1016/s0273-1177(99)00806-6
|View full text |Cite
|
Sign up to set email alerts
|

Search for hot gas in the local group with ASCA

Abstract: An X-ray study was made to examine whether some part of the soft X-ray background is coming from hot gas in the Local Group. For this purpose, four consecutive pointings were made with ASCA toward a sky region between M 31 and M 33, which is close to the direction of the center of the Local Group. By comparing the X-ray surface brightness in this sky direction with that in another blank sky region near the north equatorial pole, an upper limit on any soft excess X-ray background was determined to be 2.8×10 −9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2001
2001
2002
2002

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…where the halo gas temperature is assumed to be proportional to M T /R h (i.e., the temperature of the gas is equivalent to the virial temperature). Recent X-ray observations of the Galaxy halo by ASCA have demonstrated that the halo density within 100 kpc of the Galaxy is less than 7.62 × 10 −5 cm −5 (Osone et al 2000), which is very close to the above critical value. Therefore, the above equation implies that even if a galaxy passes through an ICM with a density two orders of magnitude lower than the central density of Coma (∼ 5.64 × 10 −3 cm −3 ), the galaxy halo gas can still be greatly affected by the ICM.…”
Section: Analytical Modelsupporting
confidence: 57%
“…where the halo gas temperature is assumed to be proportional to M T /R h (i.e., the temperature of the gas is equivalent to the virial temperature). Recent X-ray observations of the Galaxy halo by ASCA have demonstrated that the halo density within 100 kpc of the Galaxy is less than 7.62 × 10 −5 cm −5 (Osone et al 2000), which is very close to the above critical value. Therefore, the above equation implies that even if a galaxy passes through an ICM with a density two orders of magnitude lower than the central density of Coma (∼ 5.64 × 10 −3 cm −3 ), the galaxy halo gas can still be greatly affected by the ICM.…”
Section: Analytical Modelsupporting
confidence: 57%
“…Regarding the other density structure parameter, r c , Suto et al (1996) use r c = 150 kpc as does Bland-Hawthorn (1999), while Maloney & Bland-Hawthorn (1999) consider the range r c = [0, 350 kpc]. Banday & Gorski (1996) and Osone et al (2000) only restrict themselves to core radii smaller than the distance from the observer to the LGH center. For a relatively poor group like the Local Group, a value of r c = 150 kpc (again typical of clusters) seems rather large when viewed in light of observational results on other groups (Mulchaey et al 1996b;Pedersen, Yoshii, & Sommer-Larsen 1997;Dahlem & Thiering 2000).…”
Section: Density Profilementioning
confidence: 99%
“…Regarding the metallicity Z of halo gas, Z = 0.3Z ⊙ is used in all previous models when modelling the LGH X-ray emission (Suto et al 1996;Osone et al 2000), although Maloney & Bland-Hawthorn (1999) also consider Z = 0.01Z ⊙ and Z = 0.1Z ⊙ . The value Z = 0.3Z ⊙ , however, is typical of clusters and rich groups of galaxies (e.g., Hwang et al 1999) whereas poor low-temperature (T 1 − 1.5 keV) groups tend to have somewhat lower metallicities, possibly because their gravitational potentials are too shallow to retain all the enriched ejecta of the constituent galaxies (Tawara et al 1998;Davis et al 1999;Hwang et al 1999).…”
Section: Metallicitymentioning
confidence: 99%
See 2 more Smart Citations